Si3N4/graphene nanocomposites for tribological application in aqueous environments prepared by attritor milling and hot pressing. Issue 12 (September 2017) - Balázsi, Csaba; Fogarassy, Zsolt; Tapasztó, Orsolya; Kailer, Andreas; Schröder, Christian; Parchoviansky, Milan; Galusek, Dusan; Dusza, Ján; Balázsi, Katalin
Abstract: Advanced ceramic materials have proved their superior wear resistance as well as mechanical and chemical properties in a wide range of industrial applications. Today there are standard materials for components and tools that are exposed to severe tribological, thermal or corrosive conditions. The main aim of this work is to develop novel, highly efficient tribological systems on the basis of ceramic/graphene nanocomposites as well as to prove their superior quality and to demonstrate their suitability for technical applications e.g. for slide bearings and face seals in aqueous media. Current research in the field of ceramic nanocomposites shows that is possible to make ceramic materials with improved mechanical and tribological properties by incorporating graphene into the Si3 N4 structure. Multilayered graphene (MLG) was prepared by attritor milling at 10 h intensive milling of few micrometer sized graphite powders. The large quantity, very cheap and quick preparation process are a main strengths of our MLG. Si3 N4 /MLG nanocomposites were prepared by attritor milling and sintered by hot pressing (HP). The Si3 N4 ceramics were produced with 1 wt%, 3 wt%, 5 wt% and 10 wt% content of MLG. Their structure was examined by transmission electron microscopy (TEM). The tribological behavior of composites in aqueous environment was investigated and showed the decreasing character of wear at increased MLG content. This new approach is very promising, since ceramic microstructures can be designed with high toughness and provide improved wear resistance at low friction.